2006
DOI: 10.1007/s11046-005-0228-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nitric Oxide Production by Macrophages in Chromoblastomycosis: A Role for Fonsecaea pedrosoi Melanin

Abstract: Chromoblastomycosis is a chronic and progressive deep mycosis that is usually found in tropical and subtropical areas. Fonsecaea pedrosoi is considered its most frequent etiologic agent and causes a typical granulomatous inflammatory response, whose degree reflects the immune status of the host. Since macrophages play a fundamental role in the control of the infection, this study aimed at investigating the production of oxygen reactive specimens, the phagocytic capacity and the production of nitric oxide (NO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 44 publications
1
30
0
4
Order By: Relevance
“…Wang and Mazza 47) showed that various polyphenolics, compounds structurally similar to melanin, diminished the production of NO in macrophages stimulated with IFN-γ and LPS. Bocca et al 48) also found that treatment of IFN-γ and LPS-stimulated macrophages with melanin, obtained from the fungus Fonsecaea pedrosoi, inhibited NO production. The study performed by Zhang et al 49) on the pigmented cells of the Fonsecaea monophora fungus showed that iNOS expression in activated macrophages decreased after treatment with melanin in a dose-dependent manner, and these results were similar to our results.…”
Section: Resultsmentioning
confidence: 96%
“…Wang and Mazza 47) showed that various polyphenolics, compounds structurally similar to melanin, diminished the production of NO in macrophages stimulated with IFN-γ and LPS. Bocca et al 48) also found that treatment of IFN-γ and LPS-stimulated macrophages with melanin, obtained from the fungus Fonsecaea pedrosoi, inhibited NO production. The study performed by Zhang et al 49) on the pigmented cells of the Fonsecaea monophora fungus showed that iNOS expression in activated macrophages decreased after treatment with melanin in a dose-dependent manner, and these results were similar to our results.…”
Section: Resultsmentioning
confidence: 96%
“…During an inflammatory response, cells of the innate and acquired immune systems release a variety of mediators, such as nitric oxide (NO), tumor necrosis factor-α (TNF-α), interleukins (IL), and the reactive nitrogen and oxygen species, which are implicated in the pathogenesis of a number of inflammatory diseases [112]. [113] reported that treatment of macrophages activated in vitro with melanin from the fungus F. pedrosoi inhibited the production of nitric oxide and Th1 cytokines. The study performed by [114] showed that the expression of inducible nitric oxide synthase gene decreased and lower levels of cytokines, such as IL-12 and TNF-α, were observed when activated macrophages were incubated with melanized cells of the Fonsecaea monophora fungus.…”
Section: Biological Activities Of Melaninmentioning
confidence: 99%
“…Bocca et al . reported that melanin present in F. pedrosoi cells inhibits the production of nitric oxide by macrophages [87]. …”
Section: Pathomorphology and Pathophysiology Of Chromoblastomycosismentioning
confidence: 99%